A history of freedom - Fears, J. Rufus; Teaching Company ([Chantilly, VA ] : The Teaching Company, 2005)
Presents lectures delivered by J. Rufus Fears concerning the history of freedom from ancient civilization to the twentieth century
pt. 3. lecture 25. The Bill of Rights ; lecture 26. Liberty & Lee at Gettysburg ; lecture 27. Liberty & Lincoln at Gettysburg ; lecture 28. FDR & the progressive tradition ; lecture 29. Why the French Revolution failed ; lecture 30. The Liberal tradition ; lecture 31. Churchill & the war for freedom ; lecture 32. The illiberal tradition ; lecture 33. Hitler & the war against freedom ; lecture 34. The Cold War ; lecture 35. Civil disobedience & social change; lecture 36. Freedom & the lessons of history
Title from title screen
Lecturer: J. Rufus Fears
Keywords: Liberty; Civilization -- History